Variability on particulate matter and meteorology dataset during the hazy period in eastern region of Peninsular Malaysia - Ku Mohd Kalkausar Ku Yusof; Siti Sofo Ismail; Azman Azid; Muhamad Shirwan Abdullah Sani; Noorain Mohd Isa; Mohd Zulfahmie Mohamat Zawawi (Data in Brief, 2020)
This paper provides detail on sequence analysis of hazy days based on eight monitoring stations from three states (Kelantan, Terengganu and Pahang) in the eastern region of Peninsular Malaysia. The dataset comprises of 1502 daily mean hazy days that had been measured for a decade. The meteorology data namely wind speed, wind direction, air temperature, relative humidity and particulate matter (PM10) were used to comprehend the variability, and the relationship existed amongst variables. The final dataset consists of a summary descriptive analysis and a boxplot, where all five variables were involved, including the minimum, maximum, mean, 1st quartile, median, 3rd quartile and standard deviation are presented. Apart from descriptive analysis, the normality test and histogram were performed as well. Keywords: Haze, Histogram, Normality test, Meteorological, Particulate matter (PM10)